Benedicta Stahl Sodré: mulher protestante na educação brasileira - Mendes, Elieth Sodré Terence (2008)
This research, while attempting to establish a dialogue between Science of Religion and Education, brings into focus the actions and attitudes of Benedicta Stahl Sodré (1900 - 1973), moved by a spirit of self-denial and non-conformity, she contributed to steer a different path to the Brazilian educational system in the 20th Century. This work can be divided into two sets of complementary actions: historical investigation and analysis of the material gathered. The first set of actions is comprised of: 1. a presentation of the Brazilian historical background, of that time span; 2. a historical recollection of the educational movements that culminated with the adoption of differentiated methods for teaching literacy and classroom reading; and 3. the organization of biographical data, gathered or inferred from extant documents that related to or belonged to the educator being researched. The second set of action is comprised of: 1. a formal and content-wise analysis of the books published by this educator; 2. an analysis of the sequence of content and exercises proposed in her books; and 3. a description of the resources, methods and strategies adopted in this work. Both sets of actions are built, as we intend to present in this thesis, on a foundational religious conviction, which finds its concrete form in a constant search for a holistic education of the individual person. In order to demonstrate this, it is made evident that the themes and the values, which are found in the Sodré materials, can be related to beliefs and attitudes. Therefore, this work represents and opportunity of recognition of Presbyterian contribution towards changes in the educational routes in the first half of the 20th Century.